2008
DOI: 10.1111/j.1751-7176.2008.00050.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Antihypertensive Efficacy of Olmesartan Medoxomil

Abstract: The authors assessed the early antihypertensive efficacy of olmesartan medoxomil (OM) in a 12‐week prospective observational study. Of 2221 patients with untreated hypertension who received OM (mainly 10 or 20 mg), 331 patients whose blood pressure (BP) was measured at 1 week after initiation of treatment were defined as the ``early BP determination group,'' whereas the remaining 1890 patients were defined as the ``standard BP determination group.'' Baseline characteristics, doses of OM, concomitant drugs used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…16 There are substantial data showing the antihypertensive effects of OLM on CBP, but little data are available on HBP levels. 17, 18, 19, 20, 21, 22 …”
Section: Introductionmentioning
confidence: 99%
“…16 There are substantial data showing the antihypertensive effects of OLM on CBP, but little data are available on HBP levels. 17, 18, 19, 20, 21, 22 …”
Section: Introductionmentioning
confidence: 99%
“…These findings are supported by several clinical studies, including a recent secondary analysis of an open-label, prospective cohort study in Japan [15]. A total of 2221 patients received olmesartan as monotherapy (mainly at 10 mg and 20 mg doses) and their BP was determined within 3 weeks of initiating treatment.…”
Section: Article Highlightsmentioning
confidence: 77%
“…The mean BP was 147/85.6 mmHg (p < 0.0001) after 1 week in the early BP determination group (from a baseline level of 169.0/95.6 mmHg) and 146.5/84.7 mmHg (p < 0.0001) after 2 weeks in the standard BP determination group (from a baseline of 168.2/95.2 mmHg). The changes seen after 1 week in the early BP measurement group represent approximately 60 and 70% respectively of the SBP and DBP reductions seen at week 12 (31.6 and 16.7 mmHg, respectively) [15]. Such findings are supported by OLMEBEST, a large (n = 2306), multinational, multicenter study that investigated the efficacy of olmesartan 20 mg [16].…”
Section: Article Highlightsmentioning
confidence: 82%
“…Morning home BP decreased significantly after the first week of treatment. Saito et al 28 have reported that olmesartan is safe and effective in reducing clinic BP after 1 week of treatment.…”
Section: Discussionmentioning
confidence: 99%